Students’ Attitude on Learning English At Junior High Schools in Aru District - Mariana Seni; Jeny Lekatompessy (MATAI: International Journal of Language Education, 2021)
The focus of this research is the researcher wants to make a survey to investigate about student’s attitudes on Learning English. The survey has done in November 2020 to December 2020 at five junior high schools in Dobo, eight grades and the researcher also used questioner as the instrument to collect the data from the students. The questioner has divided into multiple choice to gain the information about students interest in learning English, frequency of study English in a week, read the material before class, never absent to study English, make the summaries, read English book, reread materials, submit assignment which is consist of 21 questions and the essay, it is gain about students’ like or dislike, important or not, challenges in learn English, the way to learn English with fun, attitude should be developed and suggestion for the English teacher which is consist of 5 questions. It was taken of ten students from each school. At the end of the research, the result showed that most of the students from five junior high schools in Dobo showed their positive attitude in learn English and the rest of them showed the negative attitude in learn it. It means that the students still have courage to learn English. So hopefully English should be used by students not only at school but it must be started from family, environment and school to improve their English skill.